PROMOTING MENTAL HEALTH AMONG CAREGIVERS OF PEOPLE WITH MENTAL DISORDERS DURING PANDEMIC THROUGH WHATSAPP GROUP - Ziske Maritska; Bintang Arroyantri Prananjaya; Puji Rizki Suryani; Raden Ayu Mulya Liansari; Adam Triyoga; Rizka Fathia (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Changes in all aspects of life due to the pandemic affect all levels of society without exception, including vulnerable populations such as people with mental disorders. Sudden changes in a short time can create challenges for both the patients and the families. A better understanding of the course of their illness and what preventive and promotive efforts can be made by families/caregivers during the pandemic can help improve their quality of life. Online education for caregivers/families aims to shape a better understanding of mental health and mental disorders.